Narrativa transmedia: Ponce Enriquez…tal y como es. - Garcia Ochoa, Denisse Fernanda; Vera Rueda, Wendy Xiomara (Machala, 2021)
Ponce Enríquez ... as it is, it is a transmedia proposal that seeks to promote the identity of the Camilo Ponce Enríquez canton, since for years its image has been tarnished by political conflicts, mining and the contamination that exists in the area Leaving aside the attributes and potential meanings that this territory has, therefore, it has not been given the true space for dissemination that they require. The objectives set for the development of this work are based on establishing the appropriate digital platforms to disseminate transmedia content, develop communication products based on social scenarios and analyze the efficiency of the content during the publication period. For this reason, a broad investigation of the problem is given, using quantitative and qualitative methodology, with the application of interviews, focus group, survey, observation and monitoring. During the investigation phase, there was the participation of professionals in the field of digital, cultural and narrative communication who approach the subject from theoretical and technical concepts. This group is joined by graduates in social communication who have developed transmedia projects and know the work that must be done in the field to obtain effective results with value for the object of study. As key pieces are also the inhabitants and characters of the territory who are the spokesmen for the feelings of the Ponce people, who have the need to show the diversity that their land offers, but who has been overshadowed by those problems that do not represent them. Through the information collected, the social settings that encompass each of the characteristics of this place were identified. These being My Ponce, Natural Beauty, My Roots, Fusion of Flavors and Ponceños. Each of these scenarios reflect the most characteristic of this magical azuayo that they have much to show the world. Considering these scenarios, communication products such as short, promotional videos, photographs, reports, live broadcasts and podcasts were developed, which were published on the social networks Facebook and Instagram, as well as on the Anchor Fm digital platform. In addition, to promote this proposal, a local media tour was carried out, informing the population about the importance of this transmedia narrative and their participation to make the territory visible. The results obtained were optimal, since an engagement of 13% and 130 followers were achieved on Instagram and on Facebook a 20% engagement and 418 followers, this with only 12 days of publication that occurred, under prior planning. The followers within these social networks and platform have gone from being purely consumers to prosumers, that is, they joined the proposal and assumed it as their own to build solid foundations and continue to grow in the eyes of the local, national and international audience. Undoubtedly, this transmedia narrative made a people feel their roots, their history and reconnect with the value of their land, which is more valuable than they thought or what they had been led to believe.
Ponce Enríquez…tal y como es, es una propuesta transmedia en la que se busca promover la identidad del cantón Camilo Ponce Enríquez, ya que durante años su imagen se ha visto empañada por conflictos políticos, de minera y la contaminación que existe en la zona, dejando de lado los atributos y significados potenciales que tiene este territorio, por ende, no se le ha dado el verdadero espacio de difusión que requieren. Los objetivos planteados para el desarrollo de este trabajo se basan en establecer las plataformas digitales adecuadas para difundir el contenido transmedia, elaborar productos comunicacionales en base a los escenarios sociales y analizar la eficiencia del contenido durante el periodo de publicación. Por ello se da una investigación amplia de la problemática, usando metodología cuantitativa y cualitativa, con la aplicación de entrevistas, focus group, sondeo, observación y monitoreo. Durante la fase de indagación se contó con la participación de profesionales en el ámbito de comunicación digital, cultural y de narrativa quienes abordan la temática desde conceptos teóricos y técnicos. A este grupo se suman egresadas en comunicación social que han desarrollado proyectos transmedia y conocen el trabajo que se debe hacer en campo para obtener resultados eficaces con valor para el objeto de estudio. Como piezas claves se encuentran también los habitantes y personajes del territorio que son los portavoces del sentir del pueblo ponceño, que tiene la necesidad de mostrar la diversidad que ofrece su tierra, pero que se ha opacado por aquellos problemas que no los representan. A través de la información recopilada se identificaron los escenarios sociales que engloban cada una de las características de este lugar. Siendo estos Mi Ponce, Belleza Natural, Mis Raíces, Fusión de Sabores y Ponceños. Cada uno de estos escenarios reflejan lo más caracterizo de este mágico azuayo que tienen mucho por mostrar al mundo. Considerando estos escenarios se elaboraron productos comunicacionales como videos cortos, promocionales, fotografías, reportajes, transmisiones en vivo y podcast, que fueron publicados en las redes sociales Facebook e Instagram, como también en la plataforma digital Anchor Fm. Además, para promocionar esta propuesta se realizó una gira de medios locales dando conocer a la población sobre la importancia de esta narrativa transmedia y de su participación para visibilizar al territorio. Los resultados obtenidos fueron óptimos, ya que se logró un engagement del 13% y 130 seguidores en Instagram y en Facebook un 20% de engagement y 418 seguidores, esto con tan solo 12 días de publicación que se dieron, bajo una planificación previa. Los seguidores dentro de estas redes sociales y plataforma han pasado de ser netamente consumidores a prosumidores, es decir que se unieron a la propuesta y la asumieron como suya para construir bases sólidas y seguir creciendo ante la mirada de la audiencia local, nacional e internacional. Sin duda alguna, esta narrativa transmedia logro que un pueblo sienta a sus raíces, su historia y se rencuentre con el valor de su tierra, que es más valioso de lo que pensaban o de lo que les habían hecho creer.
Keywords: IDENTIDAD TERRITORIAL; NARRATIVA TRANSMEDIA; ESCENARIO SOCIAL